Who Ordered this Baby? : Definitely Not Me! - Winkler, Henry 1945-; Oliver, Lin (New York, N.Y. : Grosset & Dunlap, 2007)
Unhappy that his parents are expecting a baby and that his birthday party will be nothing special this year, fifth-grader Hank decides to celebrate by doing his favorite things, with only his new pet tarantula, Rosa, for company.
Accelerated Reader AR
Keywords: Pregnancy -- Fiction; Brothers and sisters -- Fiction